Airborne salinity penetration in the coastal tropical climate of the Havana Cuba. - Castañeda-Valdés, Abel; Corvo-Pérez, Francisco; Howland, Juan J.; MarreroÁguila, Rigoberto (Revista CENIC Ciencias Quimicas)
Penetration of airborne salinity in a tropical coastal in Havana City where building structures constitute obstacles for entrance and distribution of the marine aerosol was studied. Chloride ions deposition in exposure site at different distances from the sea was measured. In Havana City, at a distance from the sea about 32 m, deposition of heavier and big chloride particles reaches a minimum. Average annual wind speed flow showed a higher influence on atmospheric corrosivity in the site close to the sea and without obstacles to the wind flow. Wind speed flow is not the only meteorological variable influencing on chloride ions deposition, but also temperature-humidity complex. The influence of this complex is higher in the site close to the seashore. A decrease in air temperature, due to transitory meteorological phenomena, such as the entrance of cold fronts, is the climatic factor with higher influence in chloride ions deposition in the City.